Pengaruh Penggunaan Mobile Banking Terhadap Efektivitas Dalam Pembayaran Uang Kuliah Tunggal UIN SMH Banten - Bani Khafidz; Laelatus Sa’diah Amaliah; Ahassa Nafiza Habna; Wahyu Hidayat; Zaini Ibrahim (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Mobile banking is a service provided by banks that allows customers to conduct various types of service transactions anytime and anywhere through smartphone devices. This service is not only utilized by customers at large, but UIN students have also utilized the service in making single tuition payments. However, there are still many students who have not utilized the convenience of this service. The purpose of this study was to determine the effect of the effectiveness and instruments of using mobile banking on customer satisfaction. This research uses a quantitative approach.